Valuation of Netflix - Rodriguez Lagos, Pablo Jose (2024)
This paper applies valuation methodologies such as the Discounted Cash Flow (DCF) model and Relative valuation to value Netflilx Inc. The thesis poses the following research question, does Netflix's current share price reflects its intrinsic value? The thesis provides deeper insights into Netflix from a financial and business standpoint. An industry overview is conducted for the streaming services industry while tackling Netflix's competitive positioning. In addition to this, Netflix's financial performance is analyzed by comparing its results with those of its key competitors. Their financial results are projected 10 years into the future, which will provide the neccesary data to construct a discounted cash flow model supplemented by a relative valuation, scenario analysis, ans risk analysis. The output of this analysis is a buy/hold/sell recommendation based on the "intrinsic value" of the company.